2008
DOI: 10.2165/00023210-200822070-00005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Switching Drug Formulations from Immediate-Release to Extended-Release OROS Methylphenidate

Abstract: The switch from IR to OROS methylphenidate was associated with an improvement in both adherence and effectiveness. There were no differences between IR and OROS methylphenidate in terms of tolerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
41
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 11 publications
0
41
0
2
Order By: Relevance
“…15,19 A Spanish study based on chart reviews also found that a switch from MPH IR to MPH ER was associated with both a significant reduction of ADHD symptoms and longer treatment duration and compliance. 20 There is reason to believe that superiority in efficacy and more convenient medication of ER formulations may contribute to longer duration and better compliance. However, 2 recent meta-analyses have given conflicting results about the superiority in efficacy of ER formulations over IR formulations in controlled studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…15,19 A Spanish study based on chart reviews also found that a switch from MPH IR to MPH ER was associated with both a significant reduction of ADHD symptoms and longer treatment duration and compliance. 20 There is reason to believe that superiority in efficacy and more convenient medication of ER formulations may contribute to longer duration and better compliance. However, 2 recent meta-analyses have given conflicting results about the superiority in efficacy of ER formulations over IR formulations in controlled studies.…”
Section: Discussionmentioning
confidence: 99%
“…24,40 Central stimulant dosing seems to have been generally adequate (mean, 58.9 mg/d) and in line with other naturalistic and controlled studies of CS treatment in adults. 13,20,41 More than half of the patients tried 2 or more types of CS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A comparison of extended-versus immediate-release methylphenidate in adults suggested that adherence improved after switching to the long-acting formulation 31 ; similarly, treatment duration was found to be greater among children and adolescents who initiated treatment with extended-release methylphenidate versus those who used an immediate-release formulation 32 . A comparison of persistence with long-acting methylphenidate versus short-acting methylphenidate or mixed amphetamine salts likewise supports the notion that persistence is better with long-acting than with short-acting ADHD medications 33 .…”
Section: Discussionmentioning
confidence: 99%